Inflation and global supply chain pressure in Eurozone: a time-varying causal analysis - Stan, Sebastian-Emanuel; Oprean-Stan, Camelia; Bătușaru, Cristina; Mârza, Bogdan; Bratu, Renate (Technological and Economic Development of Economy, 2025)
The aim of this paper is to analyze the causal relationship between inflation and global supply chain pressure in the Eurozone. In contrast to the full-sample causality method, this paper utilizes the bootstrap subsample rolling window causality method to account for structural changes. Initially, the computed vector autoregressive models demonstrate that the short-term relationship between inflation and global supply chain pressure is unstable. The dynamic causal relationship is reexamined in the subsample rolling window causality test using a time-varying method (RB bootstrap-based modified-LR causality test). The results indicate that inflation is influenced by the expansion of global supply chain pressure in a variety of sub-periods, with both positive and negative effects. Conversely, inflation fluctuations increase the uncertainty of the Global Supply Chain Pressure Index. The novelty of the findings is that they illustrate bidirectional causal relationships between the two variables, which is in contrast to the existing body of empirical research that does not support the direction of causality. The implications of these findings emphasize the need to implement appropriate monetary policy measures in order to mitigate the inflationary consequences of disruptions in the global supply chain and to ensure a more stable supply chain network.